Seedling Growth and Phosphorus Uptake in Response to Different Phosphorus Sources - Pirjo S. A. Mäkelä; Daniel O. Wasonga; Ainhoa Solano Hernandez; Arja Santanen (Agronomy, 2020)
Phosphorus (P) is an essential element for plant growth and development. Finding new P sources and ways to improve crop P utilization are necessary due to the depletion of phosphate reserves. Five crop species, buckwheat (Fagopyrum esculentum L.), maize (Zea mays L.), oilseed rape (Brassica napus L. ssp. oleifera (Moench) Metzg.), spelt wheat (Triticum spelta L.), and white lupine (Lupinus albus L.), were grown in pots containing sandy soil with chemical nutrients, digestate, and meat bone meal (MBM) without added nutrients. Thirty days after the seeding plants were harvested, the growth stage, soil-plant analysis development (SPAD) value, biomass, P content of the plants, colonization of the roots with endomycorrhiza, and soil pH were analyzed, and the number of fungal spores in the soil was counted. All species showed interaction with the P sources for measured traits, except for the rhizosphere pH. A high biomass was recorded in all species fertilized with various P sources compared to the unfertilized treatment. Buckwheat and spelt wheat showed a higher P uptake with MBM, and the mycorrhizal symbiosis improved with digestate or MBM compared to synthetic P. The results indicate that different species have adaptative mechanisms to various P sources which could improve the resilience and sustainability of cropping systems.